94 Histopathological response on clinicoradiological presentation and prognosis of patients with advanced high grade serous ovarian carcinoma treated with neoadjuvant chemotherapy. (18th September 2019) - Lopes, A; Nogueira D Genta, ML; da Costa Miranda, V; Mendonza Lopez, RV; Marino Carvalho, F; Paula Carvalho, J
Abstract : Objectives: To analyze the influence of histopathological response on clinicoradiological and survival of patients with high-grade serous ovarian carcinoma (HGSC) after neoadjuvant chemotherapy. Methods: From 2008 to 2016, patients with advanced HGSC (FIGO IIIC-IVB) who underwent 6 cycles of NACHT (carboplatin-paclitaxel) followed by cytoreductive surgery were reviewed and divided in 3 groups: complete pathological response (1), pathological residual tumor with complete cytoreduction (2), and sub-optimal cytoreduction (3). CA-125 and computed tomography response were classified by RECIST criteria and compared using Fisher's exact and McNemar tests, respectively. Progression-free survival (PFS) and overall survival (OS) were analyzed using Cox-proportional hazard. Results: One-hundred-one patients, median age 60 years, followed by median of 36 months, were included. Groups 1 (n=10), 2 (n=61), and 3 (n=31) presented, respectively, mean OS of 75.7 (63–88); 55 (95% CI 41–69), and 26 (95% CI 19–32) months (p = <0.004). The median DFS was 33 (27–66) and 7.7 (6–8) months for groups 1 and 2, respectively. Complete radiological response was seen in 80%, 25% and 3% (p= <0001) while normalization of CA-125 was observed in 100%, 61% and 38% on groups 1, 2 and 3, respectively (p= 0.003). OS among patients with CA-125 normalization (n=62) was higher than among non-responders (61, CI 95% 41–81 months vs. 30, CI95% 23–37 months (p=0.003). Median OS associated with complete, partial and stable/progression radiological response was 79(24–134), 35(26–43) and 30(12–48) months, respectively (p= 0.034). Conclusions: Complete histopathological response, normalization of CA-125 and complete radiological response after NACHT were associated with improved overall and disease free survival.